Enhanced H(2)O(2)-Induced Cytotoxicity in “Epithelioid” Smooth Muscle Cells: Implications for Neointimal Regression - Li, Wei-Gen (2000)
Vascular smooth muscle cells (SMCs) are phenotypically diverse. Although most medial SMCs can be classified as “fusiform,” others are of the “epithelioid” phenotype. Proliferation and apoptosis of epithelioid SMCs may contribute importantly to neointimal formation and regression, respectively. Because reactive oxygen species (ROS) are increased in vascular injury and can induce apoptosis of SMCs, we compared the effects of ROS on epithelioid and fusiform SMCs. Epithelioid and fusiform SMC lines were clonally isolated from rat aortic media and studied under similar conditions and passage numbers. H(2)O(2) produced dose- and time-dependent cytotoxicity that was enhanced in epithelioid compared with fusiform cells. After 24-hour exposure to 50 μmol/L H(2)O(2), epithelioid cell numbers were reduced by 34±5% versus a 3±5% (P<0.05) reduction in fusiform cell numbers. Similar results were obtained whether H(2)O(2) was administered to growth-arrested or growing cells or when epithelioid and fusiform cells were exposed to extracellular O(2)(·−). To investigate whether apoptosis contributed to enhanced ROS-induced cytotoxicity in epithelioid SMCs, terminal deoxyribonucleotidyl transferase (TDT)-mediated dUTP-digoxigenin nick-end labeling (TUNEL) staining was performed. The incidence of TUNEL positivity was 5-fold increased in epithelioid versus fusiform SMCs after treatment with 50 μmol/L H(2)O(2) (19±1% epithelioid versus 5±1% fusiform, P<0.05). Enhanced H(2)O(2)-induced apoptosis in epithelioid SMCs was confirmed by DNA laddering. Furthermore, when balloon-injured aortas were exposed to H(2)O(2) ex vivo, enhanced apoptosis was observed in neointimal compared with medial SMCs. These results suggest that epithelioid SMCs exhibit enhanced sensitivity to ROS-induced apoptosis, which may play an important role in neointimal regression.